Effectiveness and Challenges of Differentiated Learning in Secondary School: A systematic literature review review - Farida, Kamelia Lu’lu’ul; Baharudin , Baharudin; Sai’dy, Sai’dy; Hasanah, Uswatun (IJBLE Scientific Publications Community Inc., 2025)
This systematic review of the literature discusses the effectiveness and challenges of implementing differentiated learning (DI) in secondary schools. This study analyzed 16 articles published between 2019 and 2023 using the PRISMA protocol. The study's results indicate that DI is effective in enhancing academic achievement and student engagement, particularly in the classroom among students with diverse abilities. However, the main challenges include a lack of teacher training, limited resources, large class sizes, and insufficient planning time. The success of DI is supported by collaboration between teachers, professional training, and a positive attitude towards inclusion. This study suggests that further research is needed for the practical training of teachers and the long-term evaluation of DI, particularly in developing countries, as well as for online learning.